Development of a Workload Report to Optimize Staffing in a Transfusion Services Laboratory. (21st September 2018) - Khan, Jenna; Hoffman, Noah; Tsang, Hamilton; Pagano, Monica; Mathias, Patrick
Abstract: Transfusion services laboratories (TSLs) must at any given moment be able to provide timely blood products to patients without error. To achieve these goals of quality and safety, TSLs must have adequate staff with the appropriate skills to match patient testing requirements and blood product processing, testing, and release volumes. After discovering limitations in the standard workload reports generated by the laboratory information system (LIS) in a recently opened TSL, laboratory leadership and staff requested enhanced workload reports with the intention of optimizing laboratory staffing based on product and testing utilization patterns. To address this need, we developed data extracts for our LIS (Sunquest FlexiLab, version 7.2) that capture blood products issued (red blood cells, platelets, plasma, cryoprecipitate, and granulocytes), clinician-ordered testing (eg, type and screen, prenatal testing), laboratory add-on testing (eg, antibody identification, weak D antigen identification), and blood component preparation (eg, irradiation, volume reduction, washing). These data were used to generate reports describing order volumes per hour for each day of the week using R statistical software (version 3.3). As our TSL provides a variety of complex laboratory testing, to better represent the relative contribution of more labor-intensive testing, additional graphical displays of staff time spent per test per hour were also created. Reports are compiled in an R Markdown file for enhanced utility and reproducibility. Expected utilization patterns were observed. For example, increases in issued products in the mornings for scheduled surgeries and increases in issued platelets post the scheduled midnight blood draw for the hematology-oncology services. Reports were sensitive enough to reveal more subtle changes such as a 1-hour shift in peak time for products issued on Wednesdays, subsequently determined to be due to an operating room staff meeting on those mornings. As staffing is adjusted based on these reports, turnaround time for testing will be monitored to assess the impact and utility of these reports. Workload reports can provide a valuable tool for a data-driven approach to managing staffing requirements, and we have demonstrated a custom approach to improved reporting through targeted extraction of LIS data coupled with simple analyses in an open source software environment. Optimizing laboratory staffing will contribute to an efficient transfusion service resulting in enhanced clinical care.